1956
DOI: 10.1136/bmj.1.4973.943
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety States

Abstract: ON CHEMICAL TRANQUILLIZERS BRITISH 943 MEDICAIL JOURNAL~i However, I can only say that as a result of our recent experiences I would be sorry indeed to be without this drug again at the present time. And if frenquel, used alone or combined with E.C.T., helps only a small limited group of cases of depressions and early schizophrenics, and we can learn to pick out these groups clinically, it will still be very much worth while. Conclusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1961
1961
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The mean age of our anxious patients was considerably higher than in other reported studies by Miles, Barabee & Finesinger (1951), Wheler et al (1950), Garmany (1956), Gurney et al (1970, and this might suggest that our selection included atypical or diagnostically doubtful cases. This is particularly important to examine because Lader & Marks (1971) have suggested that anxiety which begins after the age of 40 is commonly part of a depressive syndrome.…”
Section: Chronicity Of Anxious Patientsmentioning
confidence: 57%
“…The mean age of our anxious patients was considerably higher than in other reported studies by Miles, Barabee & Finesinger (1951), Wheler et al (1950), Garmany (1956), Gurney et al (1970, and this might suggest that our selection included atypical or diagnostically doubtful cases. This is particularly important to examine because Lader & Marks (1971) have suggested that anxiety which begins after the age of 40 is commonly part of a depressive syndrome.…”
Section: Chronicity Of Anxious Patientsmentioning
confidence: 57%
“…Compared with the frequency of psychiatric disorder in one Psychiatric Out-Patients' Department (Garmany, 1956) this study showed that the incidence of depression, hysteria, and psychopathic personality was similar, while obsessional states were more frequent (10 per cent. as compared with 2 per cent.…”
Section: Materials and Methods Of Studymentioning
confidence: 66%
“…Treatment was by superficial psychotherapy aimed at resolving the conscious or near conscious conflicts (Garmany, 1956) which aroused guilt and other feelings. Macalpine (1957) pointed out that reassurance is not helpful in the face of deep convictions about venereal disease, and it has been stressed that detailed history taking with sympathetic interrogation is worth many hours of attempted reassurance (Puig, 1946;Grimble, 1961).…”
Section: Discussionmentioning
confidence: 99%